2008
DOI: 10.1117/12.770202
|View full text |Cite
|
Sign up to set email alerts
|

Mammography workstation design: effect on mammographer behaviour and the risk of musculoskeletal disorders

Abstract: In the UK Breast Screening Programme there is a growing transition from film to digital mammography, and consequently a change in mammography workstation ergonomics. This paper investigates the effect of the change for radiologists including their comfort, likelihood of developing musculoskeletal disorders (MSD's), and work practices. Three workstations types were investigated: one with all film mammograms; one with digital mammograms alongside film mammograms from the previous screening round, and one with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Taylor-Phillips et al 12 found in live screening that the screen readers used the prior mammograms for a greater proportion of cases when these were digitised in comparison to being displayed in film format on a multi-viewer. In the present study eye movement data have been recorded of how each participant visually examined the digital images or the digital and analogue images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor-Phillips et al 12 found in live screening that the screen readers used the prior mammograms for a greater proportion of cases when these were digitised in comparison to being displayed in film format on a multi-viewer. In the present study eye movement data have been recorded of how each participant visually examined the digital images or the digital and analogue images.…”
Section: Discussionmentioning
confidence: 99%
“…8 Taylor-Phillips et al 12 found that participants used the prior mammograms for a greater proportion of cases when they were digitised rather than when displayed in film format. The aim of the current paper is to investigate whether this difference in behaviour, when considered alongside the other factors above, will translate to a difference in screening performance.…”
Section: Introductionmentioning
confidence: 99%
“…The RULA method was used. It was determined that no more MSDs developed as a result of performing the mammograms digitally [222].…”
Section: • Radiologymentioning
confidence: 99%